THE ORIGIN AND DEVELOPMENT OF THE SCIENCE OF RELIGION (Scientific journal of the Fergana State University, 2023)
In the new period of our development, religious and national values are developing further, special attention is being paid to the deep study and analysis of the religious and educational heritage of our ancestors, and the worthy continuation of their scientific traditions. Religious studies is one of the sciences that includes the cultural, educational, and intellectual history of humanity among humanities. This article analyzes the emergence of the science of religion and the processes related to it.